ANALYSIS OF CUSTOMER SATISFACTION IN COOPERATIVE SERVICES USING THE FUZZY MAMDANI METHOD: A CASE STUDY OF KOMIDA AJIBARANG - Romantica, Krishna Prafidya; Nugraha, Agung (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to analyze customer satisfaction at KOMIDA Cooperative Ajibarang by examining the influence of two main factors, namely loan products and service quality. The research adopts a descriptive quantitative approach utilizing the Fuzzy Mamdani inference system for data processing. Data were collected through structured questionnaires and interviews with active cooperative members as respondents. The use of fuzzy logic methods was chosen due to their ability to handle uncertainty and subjectivity in customer perceptions, thereby producing results that more accurately reflect real conditions in the field. The findings reveal that both the offered loan products and the quality of services provided play equally important roles in shaping customer satisfaction. Loan products were assessed as relevant to members’ needs, while services characterized by friendliness, efficiency, and clear communication enhanced the positive experience of members in interacting with the cooperative. Most respondents gave positive, indicating that the cooperative’s services and products have met, and in many cases closely aligned with, their expectations.